Pledged Collateral Market's Role in Transmission to Short-Term Market Rates - Singh, Manmohan (IMF Working Papers; Working Paper, 2019)
In global financial centers, short-term market rates are effectively determined in the pledged collateral market, where banks and other financial institutions exchange collateral (such as bonds and equities) for money. Furthermore, the use of long-dated securities as collateral for short tenors-or example, in securities-lending and repo markets, and prime brokerage funding-impacts the risk premia (or moneyness) along the yield curve. In this paper, we deploy a methodology to show that transactions using long dated collateral also affect short-term market rates. Our results suggest that the unwind of central bank balance sheets will likely strengthen the monetary policy transmission, as dealer balance-sheet space is now relatively less constrained, with a rebound in collateral reuse.